Efficacy of anti-calcitonin gene-related peptide monoclonal antibodies in hemiplegic migraine: a case report and review of literature - Héja, Máté; Oláh, László (Frontiers in Neurology, 2025)
Hemiplegic migraine (HM) is a rare subtype of migraine with aura characterized by transient unilateral motor weakness during attacks. Although monoclonal antibodies (mABs) targeting the calcitonin gene-related peptide (CGRP) pathway have shown efficacy in migraine prevention, their role in HM remains largely unexplored, since these patients are generally excluded from randomized clinical trials aimed at developing migraine preventive drugs. We present a case of a middle-aged woman with chronic migraine and recurrent hemiplegic episodes treated with fremanezumab. After 11 months of monthly 225 mg subcutaneous fremanezumab injections, the patient experienced a substantial reduction in monthly headache days, aura episodes, and symptom severity, without safety concerns. This case adds to the emerging evidence supporting CGRP mABs as a potential therapeutic option for HM. Further research is needed to elucidate their precise mechanism and determine their efficacy in broader HM populations.